2004
DOI: 10.1289/ehp.6976
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Composition and Toxicity of Motor Vehicle Emission Samples

Abstract: In this study we investigated the statistical relationship between particle and semivolatile organic chemical constituents in gasoline and diesel vehicle exhaust samples, and toxicity as measured by inflammation and tissue damage in rat lungs and mutagenicity in bacteria. Exhaust samples were collected from “normal” and “high-emitting” gasoline and diesel light-duty vehicles. We employed a combination of principal component analysis (PCA) and partial least-squares regression (PLS; also known as projection to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(40 citation statements)
references
References 33 publications
0
40
0
Order By: Relevance
“…This can be attributed to its postulated impacts on the global climate (Novakov and Penner, 1993;Kanakidou et al, 2005) and on human health (McDonald et al, 2004;Metzger et al, 2004). The carbonaceous aerosol contains a large number of organic species, but the majority remains yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…This can be attributed to its postulated impacts on the global climate (Novakov and Penner, 1993;Kanakidou et al, 2005) and on human health (McDonald et al, 2004;Metzger et al, 2004). The carbonaceous aerosol contains a large number of organic species, but the majority remains yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of motor vehicle exhaust is partly because it consists of organic compounds and oxidant gases that are thought to contribute to the inflammatory and other effects of inhaled particles. 12,13 Generally, traffic is the primary source of UFPs in urban areas and near busy roadways. 14 -22 Cohort studies have typically reported a much higher risk for cardiovascular events for people who live within 150 m of a major highway.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] The Mexican Health Bureau, Secretaría de Salud, revised the previous National Ambient Air Quality for particles 12 establishing a 24-hr average concentration limit of 65 g m Ϫ3 and an annual average concentration of 15 g m Ϫ3 for PM 2.5 and also modified the PM with aerodynamic diameter of less than 10 m (PM 10 ) 24-hr average concentration limit to 120 g m…”
Section: Introductionmentioning
confidence: 99%